2014
DOI: 10.1371/journal.pone.0101138
|View full text |Cite
|
Sign up to set email alerts
|

Association of TNF-α, TNFRSF1A and TNFRSF1B Gene Polymorphisms with the Risk of Sporadic Breast Cancer in Northeast Chinese Han Women

Abstract: BackgroundThe interaction of tumor necrosis factor-α (TNF-α) with its receptors: TNFRSF1A and TNFRSF1B is critical for the promotion of tumor growth, invasion and metastasis. To better understand the roles of single nucleotide polymorphisms (SNPs) in the TNF-α, TNFRSF1A and TNFRSF1B genes in the development of breast cancer, we explored the associations between SNPs in these three genes and breast cancer susceptibility in northeast Chinese Han women.Methodology/Principal FindingsThis case-control study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…Both SNPs have previously been implicated in numerous complex human diseases including sporadic breast cancer (Xu et al 2014), inflammatory demyelinating disease (Park et al 2013) and ankylosing spondylitis (Davidson et al 2011). We based our SNP selection on the following criteria: (1) SNPs should have been validated by both the HapMap project and the 1000 genomes project in Caucasian populations; (2) SNPs should have a high minor allele frequency (MAF) (i.e.…”
Section: Snp Selectionmentioning
confidence: 99%
“…Both SNPs have previously been implicated in numerous complex human diseases including sporadic breast cancer (Xu et al 2014), inflammatory demyelinating disease (Park et al 2013) and ankylosing spondylitis (Davidson et al 2011). We based our SNP selection on the following criteria: (1) SNPs should have been validated by both the HapMap project and the 1000 genomes project in Caucasian populations; (2) SNPs should have a high minor allele frequency (MAF) (i.e.…”
Section: Snp Selectionmentioning
confidence: 99%
“…Five of these loci were previously reported to have variable association with the risk of single primary colorectal cancer; rs1061624 of TNFRSF1B, rs1059234 of P21, and rs9344 of CCND1 were found to reduce the risk of colorectal cancer and exert protective effects, while rs28362491 of NFKB1 and rs3212986 of ERCC1 increased the risk of colorectal cancer. Among the other 30 loci, five (rs7566, rs887574, rs13035, rs1799757, and rs5343) are reported for the first time in this study, while 25 were associated with malignant tumor development and the response to chemoradiotherapy (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33), inflammatory bowel disease (34), autoimmune diseases (35,36), vitiligo (37), insulin resistance (38), coronary heart disease, stroke, and other types of cardiovascular and cerebrovascular disease (39,40).…”
Section: Discussionmentioning
confidence: 73%
“…[915] Characteristics of the included studies are shown in Table 1. All studies used healthy volunteers or blood donors as control subjects.…”
Section: Resultsmentioning
confidence: 99%